Teaching Foreign Languages in an Era of Globalization: Introduction. Issue 1 (March 2014) - Kramsch, Claire
<x xml:space="preserve">Abstract</x> Through its mobility of people and capital, its global technologies, and its global information networks, globalization has changed the conditions under which foreign languages (FLs) are taught, learned, and used. It has destabilized the codes, norms, and conventions that FL educators relied upon to help learners be successful users of the language once they had left their classrooms. These changes call for a more reflective, interpretive, historically grounded, and politically engaged pedagogy than was called for by the communicative language teaching of the eighties. This special issue will explore how we are to conceive of such a pedagogy.